A new introduction to legal method - Cliteur, P. B.; Ellian, Afshin, 1966- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"A New Introduction to Legal Method provides a comprehensive overview of legal science, and the scientific character of legal knowledge. In five chapters, the book analyses and explores: (i) legal methodology in general, the main features of different schools of thought, and the nature of science in general; (ii) American Realism, which offers an ideal starting point for law students to reflect on the material they are about to study critically; (iii) rationalism, empiricism, and logical positivism, in particular the work of Karl Popper; (iv) criticisms of essentialism; (v) the ideological and philosophical background of contemporary liberal interpretation. The inclusion of Dutch, French and German literature sources makes this law title differ from previous writings on legal science. This textbook is ideal for students of legal method, and will be of great interest to those studying legal science, jurisprudence, legal research and legal skills"--
Is legal science a real science? -- American realism -- Rationalism, empiricism, and logical positivism: a methodological journey through a permanent reversal of doubt and certainty -- Popper's Critique of essentialism and the scientific outlook -- Three types of legal interpretation.
Includes bibliographical references and index.
Keywords: Law -- Methodology